2005
DOI: 10.1002/mrm.20673
|View full text |Cite
|
Sign up to set email alerts
|

Integrated data acquisition and processing to determine metabolite contents, relaxation times, and macromolecule baseline in single examinations of individual subjects

Abstract: Absolute quantitation of clinical 1H-MR spectra is virtually always incomplete for single subjects because the separate determination of spectrum, baseline, and transverse and longitudinal relaxation times in single subjects is prohibitively long. Integrated Processing and Acquisition of Data (IPAD) based on a combined 2-dimensional experimental and fitting strategy is suggested to substantially improve the information content from a given measurement time. A series of localized saturation-recovery spectra was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(127 citation statements)
references
References 23 publications
6
113
1
Order By: Relevance
“…The values of the metabolite concentration and T 2 obtained in the white and grey matter of control subjects were in agreement with those reported in the literature (2,3,10,19,(25)(26)(27)(28)(29), which however demonstrate a degree of variability. Most authors used an implementation of the MSM method to fit their data, and we used this approach as the gold standard for our experimental factor analysis.…”
Section: Ip Protocolsupporting
confidence: 89%
See 1 more Smart Citation
“…The values of the metabolite concentration and T 2 obtained in the white and grey matter of control subjects were in agreement with those reported in the literature (2,3,10,19,(25)(26)(27)(28)(29), which however demonstrate a degree of variability. Most authors used an implementation of the MSM method to fit their data, and we used this approach as the gold standard for our experimental factor analysis.…”
Section: Ip Protocolsupporting
confidence: 89%
“…The use of a whole-metabolite model function allows easier handling of prior knowledge (6), but it may also introduce a bias into the assessment of the metabolites due to the effect of J-coupling modulation (9), or differences in T 2 between resonances in individual metabolites (10). Fitting the singlet peaks separately can reduce the variance of the estimated singlet amplitudes, but at the cost of increasing the amplitude covariance in areas of spectral overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, one study showed that there was a significant relation between T1 and T2 of various metabolites and age. For example, T2 of NAA showed a significant increase with age (Kreis et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Given that metabolite signals in a proton MR spectrum usually have considerable overlap that makes the quantification difficult, generally, one of three different approaches is taken: 1) use of a single non-specific one-dimensional spectrum (e.g. a localized short echo time (TE) spectrum) followed by linear combination model fitting based on prior knowledge about the constituent metabolites and spectral parameters (Provencher, 1993;Ratiney et al, 2005;Slotboom et al, 1998;Wilson et al, 2011), or 2) use of a dedicated (socalled editing) one-dimensional experiment optimized for exclusive or selective sensitivity for a single metabolite of interest, usually followed by simple model peak fitting or signal integration (Allen et al, 1997), or 3) use of a standard localized two-dimensional MR spectrum followed by peak integration (Thomas et al, 1996;Thomas et al, 2001) or prior knowledge fitting Gonenc et al, 2010;Kiefer et al, 1998;Kreis et al, 2005;; Thomas et al, 2008;van Ormondt et al, 1990;Vanhamme et al, 1999). In cases 1 and 3, the choice of experimental parameters like TE and repetition time (TR) is most often based on general considerations about maximum signal for given relaxation times, insensitivity to changes in relaxation times or arguments about minimization of macromolecular baseline contributions, while in case 2 the signal yield of wanted and unwanted metabolites and their relative overlap is modeled based on quantum mechanical simulations or solution measurements.…”
Section: Introductionmentioning
confidence: 99%